Pelatihan dan Pendampingan Pembuatan Pupuk Organik Cair Berbahan Dasar Daun Kelor - Darmawan, Dery Anugerah; Ansori, Ansori; Khoiri, Syaiful (Jurnal Ilmiah Pangabdhi, 2023)
Many Indonesian people work as farmers, namely 40.6 million people. In Madura, one of the areas where the people work as farmers is Telang Village, Kamal District, Bangkalan Regency. Farmers in Telang Village are still heavily dependent on the use of synthetic chemical fertilizers because they are used to using it accompanied by synthetic chemical fertilizers which are subsidized by the government, but farmers still have difficulty accessing this assistance. The main objective of this community service activity is to increase public knowledge about organic fertilizer and skills in making liquid organic fertilizer (POC) made from Moringa leaves. The method of implementing this service consists of preparation, implementation, monitoring, and evaluation. The results obtained are that people understand the manufacture of liquid organic fertilizer made from Moringa leaves and their benefits for plants. The POC that has been successfully made has the characteristics of no foul smell, brown color, no contamination, and white precipitate. This program implies that people can make their own POC and apply it to cultivated plants. In general, farmers’ knowledge and skills are increasing